Novel Synergistic Mechanism for Lignocellulose Degradation by a Thermophilic Filamentous Fungus and a Thermophilic Actinobacterium Based on Functional Proteomics - Shi, Zelu; Han, Chao; Zhang, Xiujun; Tian, Li; Wang, Lushan (Frontiers in Microbiology, 2020)
Effective artificial microbial consortia containing microorganisms with desired biological functions have the potential to optimize the lignocellulose-based bioindustry. Thermobifida fusca was a dominant actinobacterium in high-temperature corn stalk composts, but it was unable to grow alone in corn stalk solid medium. Interestingly, T. fusca showed good growth and secreted enzymes when cocultured with Thermomyces lanuginosus. T. lanuginosus grew firstly during the initial stage, whereas T. fusca dominated the system subsequently during cocultivation. The secretome indicated that T. lanuginosus mainly degraded xylan by expressing a GH11 xylanase (g4601.t1, GeneBank AAB94633.1; with relative secretion of 4.95±0.65%). T. fusca was induced by xylan mainly to secrete a xylanase from GH11 family (W8GGR4, GeneBank AHK22788.1; with relative secretion of 8.71±3.83%) which could rapidly degrade xylan to xylo-oligosaccharide (XOS) and xylose within 2 minutes, while high concentrations (>0.5%, w/v) of XOS or xylose suppressed the growth of T. fusca; which may be the reason why T. fusca unable to grow alone in corn stalk solid medium. However, T. lanuginosus could utilize the XOS and xylose produced by xylanases secreted by T. fusca. During the synergistic degradation of lignocellulose by T. lanuginosus and T. fusca, xylan was rapidly consumed by T. lanuginosus, the residual cellulose could specifically induced T. fusca to express a GH10 xylanase with a CBM2 domain (Q47KR6, GeneBank AAZ56956.1; with relative secretion of 5.03±1.33%) and 6 cellulases (2 exocellulases and 4 endocellulases). Moreover, T. lanuginosus increased the secretion of cellulases from T. fusca by 19–25%. The order of T. lanuginosus and T. fusca was consistent with the multilayered structures of lignocellulose and could be regulated by different concentrations of XOS and xylose. The novel synergism of T. lanuginosus and T. fusca gave a new sight for revealing more synergetic relationships in natural environments and exploring efficient microbial inoculants and enzyme cocktails for lignocellulose degradation.